The diversification of the basic leucine zipper family in eukaryotes correlates with the evolution of multicellularity. Issue 1 (December 2016) - Jindrich, Katia; Degnan, Bernard
Abstract Background Multicellularity evolved multiple times in eukaryotes. In all cases, this required an elaboration of the regulatory mechanisms controlling gene expression. Amongst the conserved eukaryotic transcription factor families, the basic leucine zipper (bZIP) superfamily is one of the most ancient and best characterised. This gene family plays a diversity of roles in the specification, differentiation and maintenance of cell types in plants and animals. bZIPs are also involved in stress responses and the regulation of cell proliferation in fungi, amoebozoans and heterokonts. Results Using 49 sequenced genomes from across the Eukaryota, we demonstrate that the bZIP superfamily has evolved from a single ancestral eukaryotic gene and undergone multiple independent expansions. bZIP family diversification is largely restricted to multicellular lineages, consistent with bZIPs contributing to the complex regulatory networks underlying differential and cell type-specific gene expression in these lineages. Analyses focused on the Metazoa suggest an elaborate bZIP network was in place in the most recent shared ancestor of all extant animals that was comprised of 11 of the 12 previously recognized families present in modern taxa. In addition this analysis identifies three bZIP families that appear to have been lost in mammals. Thus the ancestral metazoan and eumetazoan bZIP repertoire consists of 12 and 16 bZIPs, respectively. These diversified from 7 founder genes present in the holozoan ancestor. Conclusions Our results reveal the ancestral opisthokont, holozoan and metazoan bZIP repertoire and provide insights into the progressive expansion and divergence of bZIPs in the five main eukaryotic kingdoms, suggesting that the early diversification of bZIPs in multiple eukaryotic lineages was a prerequisite for the evolution of complex multicellular organisms.